Case technology as one of the modern methods of teaching in higher education institutions for the competence of future professionals - Пустовойт, Б. А.; Федяй, І. О. (Scientific notes of the pedagogical department, 2018)
In the information society, to which the development of modern civilization is directed, information is of strategic value along with material and energy resources. Modern information technologies that allow to create, store, process information and provide effective ways to present it to the consumer are powerful tools for accelerating progress in all spheres of the development of society, determining the competitiveness of the country, region, industry, separate organization or educational institution. An important role in the process of creating and using information technologies belongs to the system of higher education as the main source of highly qualified personnel and a powerful base of fundamental and applied scientific research. The specificity of higher education is that it is, on the one hand, a consumer, and on the other, an active producer of information technology.